KONSEP MENGHADAP NOTARIS DALAM PEMBUATAN AKTA BERDASARKAN PERKEMBANGAN CYBER NOTARY - Christine Willyam Hutapea; Rahmida Erliyani; Anang Shophan Tornado (LPPM STIH Awang Long, 2023)
This research discusses the concept of facing a notary in making a deed based on the development of Cyber Notary. The problem is the development of the concept of facing a notary in the era of cyber notary advancement at this time and policy formulation on the concept of facing a notary in making a deed virtually in the future. The method used is normative legal research with Reform Oriented Research type. The results of the analysis, First, the concept of facing a notary is listed in Article 16 paragraph (1) letter m while Cyber Notary is listed in Article 15 paragraph (3) of the Notary Position Law. The renewal of the concept of facing in the Cyber Notary Era is a consideration of utilizing electronic media by teleconference (virtual). However, when interpreting